The Influence of Digital Marketing, Online Customer Reviews and Promotions on Purchasing Decisions for Shopee E-Commerce Users in East Pejaten - May Juwita; Tri Waluyo; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
The purpose of this study was to find out and analyze the influence of digital marketing, online customer reviews and promotions on purchasing decisions for Shopee e-commerce users in East Pejaten. With a total of 100 respondents through a questionnaire with quantitative methods and data were analyzed using multiple linear regression and assisted using the Statistical Package for the Social Science (SPSS) 23.0 application with the results showing that the variable: digital marketing (X1) has a direct effect on purchasing decisions, there is. online customer reviews (X2) have a positive and significant effect on purchasing decisions and promotions (X3) have a positive and significant effect on purchasing decisions.